Bird Flu, the OIE, and National Regulation : The WTO's India–Agricultural Products Dispute - Bown, Chad P. (Cambridge University Press, 2016)
This paper provides a legal-economic assessment of issues arising in the Panel Report over the WTO's India–Agricultural Products dispute, one of a growing list of disputes arising at the intersection of the WTO and domestic regulatory policy over human, animal, or plant health. This dispute featured allegations that India's import measures applied against avian influenza- (AI-) infected countries over poultry and related products were too restrictive, in light of the World Organisation for Animal Health's (OIE's) scientifically motivated standards and guidelines. We rely on insights from a set of economic models of commercial poultry markets in the presence of negative externalities such as AI. We use such models to motivate critical tradeoffs arising at the intersection of government regulatory regimes designed to deal with AI and how they fit alongside trade agreements such as the WTO and standard-setting bodies such as the OIE, which combine to impose constraints on regulatory and trade policy. While we find the institutional design of the OIE to be well-motivated and we are in broad agreement with the overall thrust of the Panel Report in the dispute, we also highlight a number of subtle issues which pose long-term challenges for the multilateral trading system's ability to balance trade rules with public health concerns.